Do gait parameters improve after botulinum toxin injections in post stroke patients? A prospective study. (September 2021) - Varvarousis, Dimitrios N.; Dimopoulos, Dimitris; Vasileiadis, George I.; Manolis, Ioannis; Ploumis, Avraam
Abstract: The intramuscular injection of botulinum toxin is one of the most efficient ways to treat localized spasticity in patients suffering from Central Nervous System lesions like stroke, cerebral palsy and multiple sclerosis. The gait analysis based on kinetics and kinematics is a recognized way of measurement of the effect of intramuscular injection of botulinum toxin in spastic patients suffering from chronic stroke. The aim of this study is to provide evidence of the beneficial effect of botulinum toxin on characteristics of gait pattern on patients suffering from chronic stroke. So, thirteen patients with spasticity due to chronic stroke were included in the protocol and were treated by botulinum toxin injections in the lower extremity. All patients were evaluated before the injection as well as one month after the botulinum injection on a foot pressure sensitive walkway with a power plate and by the readings of seven inertial measurements units which recorded spatio-temporal specific parameters during walking, and the spasticity was measured according to modified Ashworth Scale. While all spatio-temporal parameters of motion analysis and balance improved for most of the patients after botulinum toxin injection, only one parameter, the normal to hemiplegic step length, reached statistical significant improvement (p < 0.03). Moreover the modified Ashworth score was statistically improved post injection (p < 0.001). In conclusion the use of botulinum toxin injections is beneficial in post stroke patients as this is depicted in gait parameters improvement which accompanies the spasticity reduction. Graphical abstract: Image 1 Highlights: Below-knee intramuscular botulinum toxin injections of post stroke patients benefited both gait parameters and spasticity. The performance of the affected leg was depicted both in the stance and swing phase of the gait cycle. Botulinum toxin injections improved significantly the normal to hemiplegic step length (swing phase of hemiplegic leg). The combination of platform pressure sensors and motion IMUs offers a comprehensive gait analysis.